2008
DOI: 10.1128/jcm.02273-07
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mucoid Exopolysaccharide Production by Members of the Burkholderia cepacia Complex

Abstract: We demonstrate that all nine species of the Burkholderia cepacia complex can express the mucoid phenotype. A survey of clinical isolates showed that strains of B. cenocepacia, the most virulent species of the complex, are most frequently nonmucoid. Additionally, isolates from patients with chronic infections can convert from mucoid to nonmucoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 18 publications
8
126
0
Order By: Relevance
“…The variants and the environmental isolates of B. ambifaria produce more EPSs than the clinical isolates, a result that is in agreement with the data from Zlosnik et al (2008). In that study, 92.5% of the B. ambifaria environmental strains were frankly mucoid, whereas the clinical strain CEP0996 was not.…”
Section: Phase Variation and Adaptation In B Ambifaria L Vial Et Alsupporting
confidence: 81%
See 3 more Smart Citations
“…The variants and the environmental isolates of B. ambifaria produce more EPSs than the clinical isolates, a result that is in agreement with the data from Zlosnik et al (2008). In that study, 92.5% of the B. ambifaria environmental strains were frankly mucoid, whereas the clinical strain CEP0996 was not.…”
Section: Phase Variation and Adaptation In B Ambifaria L Vial Et Alsupporting
confidence: 81%
“…In that study, 92.5% of the B. ambifaria environmental strains were frankly mucoid, whereas the clinical strain CEP0996 was not. Interestingly, B. cenocepacia strains, the most virulent species of the Bcc, are generally nonmucoid (Zlosnik et al, 2008). This would suggest that EPS production is not a feature of CF lungs colonization, in contrast with P. aeruginosa.…”
Section: Phase Variation and Adaptation In B Ambifaria L Vial Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…The EPSs of Burkholderia species have recently been comprehensively reviewed (Goldberg, 2007). Recent studies (Zlosnik et al, 2008) have also challenged the previous belief that mucoid, EPS-producing colonial morphotypes of Bcc are rare in both environmental and clinical isolates (Govan & Deretic, 1996). Other studies have shown that mucoid Bcc isolates mostly synthesize one type of EPS, with a highly branched heptasaccharide repeating unit, which was named cepacian (Moreira et al, 2003;Sist et al, 2003).…”
Section: Introductionmentioning
confidence: 80%